Need for Artificial Groudwater Recharge: Vital Role of Surface Irrigation Works - Dhawan, B.D. (Journal of Soil and Water Conservation, 2022)
Hydrologists in variably emphasise hydrological linkages of water bodies, but without a precise quantification of their economic implications. Our limited attempt to quantify these reveals interesting results with regard to the beneficial role of canal waters in improving groundwater regime and groundwater-based agriculture in water-short regions. These waters have boosted the groundwater-based farming both in terms of number of sustainable wells and crop output per well. At least half of the state output from private tubewell irrigation in Punjab can be confidently attributed to groundwater that is of canal origin. In Tamil Nadu state, both canals and tanks together make a substantial augmentation to its natural groundwater availablility. Somewhere between one-fourth and two-fifths of the total output of the wells established in the state may be traced to seeped-in waters of canal' tank origin. These findings should set at rest the controversy about surface versus groundwater irrigation for low and medium rainfall regions.